Beyond Hope and Fear: The Effects of Organizational Theatre on Empowerment and Control - Badham, R.; Carter, W.; Matula, L.; Parker, Sharon; Nesbit, P. (Sage Publications, Inc., 2016)
Organizational theatre interventions have become established as a pervasive and influential arts-based method of dialogic organizational development, yet their effects are controversial and contested. While they have been praised for their potential as a tool of empowerment, they have also been criticized for their possible use as a more or less insidious form of control. This article explores and evaluates such claims and counterclaims, supported by an in-depth longitudinal quasi-experimental field study of customer service staff in a regional Australian bank. The results of the field study not only indicate that organizational theatre interventions may increase both empowerment and control but also suggest that the outcomes may be more lightweight than supporters have hoped and critics have feared. The article outlines the implications of these findings for future research and practice.